Numerical Verification of Empirically Designed Support for a Headrace Tunnel - Akram, Mian Sohail; Ahmed, Luqman; Ullah, Muhammad Fahad; Rehman, Faisal; Ali, Muhammad (Civil Engineering Journal, 2018)
In this paper, we used two empirical rock classification systems of rock mass rating (RMR) and rock quality tunnelling index (Q-system) for the support design of a tunnel in District Battagram, Khyber Pakhtunkhwa, Pakistan. Along the tunnel route, the rocks of Precambrian namely Gandaf Formation, Karora Formation and Besham Complex were exposed. During the field investigations, two shear zones were marked in the schist of Karora Formation. The discontinuities parameters collected during the field investigations, results of laboratory testing and material constants determined from RocData version 5.0 software were used during the empirical classification and numerical modelling. The support was designed for the rock mass units from RMR and Q. The quantification of the thickness of plastic zone and total displacement around the tunnel were achieved by the numerical modelling of RS2 9.0 software in both unsupported and supported conditions. The empirically designed support was installed in the model prepared in the RS2 software. According to the results, the empirically designed support when installed in models prepared in RS2 significantly reduced the plastic zone around the tunnel. The reduction in the plastic zone and displacement around the tunnel verified the support design by empirical methods. The present research concludes that empirical designed support can be used for the complex geology of Pakistan.